Negotiating informed consent: A students-as-partners perspective - Rifenburg, J. Michael; Pridgen, Emily (International Journal for Students as Partners, 2020)
Building on our 2019 ISSOTL poster presentation, we (Michael: a tenured English Department faculty member; and Emily: an undergraduate English major) are developing a reflective essay about our in-progress SaP project designed to assess the effectiveness of recent university system mandated curricular changes to multiple sections of an introductory college-level writing course at our home institution, the University of North Georgia, USA. Even though we received the necessary institutional and federal government permissions to conduct this research, and even though the research participants signed the necessary informed consent document, as we continue our data collection we wonder how we might better listen and watch for what Bivens (2018) calls “microwithdrawals of consent.” Bivens describes this phenomenon as the “implied or partial halt of a person’s willingness to participate in one or more aspects of the research process and the researcher’s awareness of that withdrawal.” Bivens calls on researchers to stay attuned to the participant’s body language and vocal tone to notice when participants may want to withdraw consent but not explicitly say so. When undergraduate researchers conduct interviews with other undergraduates, they are well-positioned to perceive these microwithdrawals of consent. With Emily as the lead author for this proposed piece, we wonder: How can students working in partnership with faculty help faculty better understand how informed consent is an on-going and negotiated process that does not end when research participants sign a consent document? Pondering this question emphasizes the “messy, ‘work in progress’ nature of SaP” (Matthews, 2017, p. 4), which, we argue should hold a central place in our SaP publications.